Mycobacterium tuberculosis escapes from the phagosomes of infected human osteoclasts reprograms osteoclast development via dysregulation of cytokines and chemokines. Issue 1 (10th September 2013) - Hoshino, Akiyoshi; Hanada, Sanshiro; Yamada, Hiroyuki; Mii, Shinji; Takahashi, Masahide; Mitarai, Satoshi; Yamamoto, Kenji; Manome, Yoshinobu
Abstract Spinal tuberculosis is a condition characterized by massive resorption of the spinal vertebrae due to the infection with Mycobacterium tuberculosis (Mtb). However, the pathogenesis of spinal tuberculosis has not been established because it was almost completely eradicated by the establishment of antibiotic treatment in the mid‐20th century. In this study, we investigated the inflammatory responses of human multinucleated osteoclasts infected with virulent Mtb strain. We found that the intracellular Mtb infection of multinuclear osteoclasts resulted in the rapid growth of Mtb and an osteolytic response, rather than inflammation. In response to Mtb infection, the mononuclear osteoclast precursors produced proinflammatory cytokines including tumor necrosis factor (TNF)‐α, an intrinsic characteristic they share with macrophages. In contrast, highly fused multinucleated osteoclasts incapacitated the production of these cytokines. Instead, the intracellular Mtb inside multinuclear osteoclasts escaped from the endosome/phagosome, leading to a different pattern of osteoclast activation, with the production of chemokines such as CCL5, CCL17, CCL20, CCL22, CCL24, and CCL25. Moreover, intracellular infection with an avirulent Mtb strain resulted in diminished production of these chemokines. These findings indicate that intracellular Mtb infection in multinuclear osteoclasts reprograms osteoclast development via the dysregulation of cytokines and chemokines.